I Engaging User Testing: Lessons Learned From Inpatients and Health Care Providers. Issue 3 (July 2015) - Tzeng, Huey-Ming; Yin, Chang-Yi; Fitzgerald, Kara; Graham, Katherine
Abstract : This user-testing study assessed the feasibility of the functional prototype of an innovative fall prevention intervention, i Engaging, to engage patients in their own fall prevention care during hospital stays. The i Engaging application as well as its approaches to engage patients in fall prevention care during hospital stays was perceived as being easy to use, effective, and practical. The user-testing study consisted of adults 65 years of age or older and health care providers. Abstract : Supplemental Digital Content is Available in the Text.